2
$\begingroup$

I have a question related to this and a second post. I want to calculate the codifferential under a conformal metric change, $g_\psi = e^{2\psi} g$. By Besse's book on Einstein manifolds, or an obvious calculation, we have that (acting on $p$-forms)

$$*_{g_\psi} = e^{(n-2p)\psi} *_g.$$

The codifferential is then given by

$$\delta^{g_\psi} = e^{-2\psi} \left( \delta - (n-2p) \iota_{\nabla \psi}\right).$$

But I don't end up with the correct factor in front of the brackets.

By definition, $\delta = *^{-1} \mathbf d \ *$. So, for some $\alpha \in \Omega^p(M)$ locally (consider a fixed multi-index for the moment), \begin{align*} \delta^{g_\psi} \alpha &= *_{g_\psi}^{-1} \mathbf d *_{g\psi} \left(\alpha_i \mathrm dx^i\right)\\ &= *_{g_\psi}^{-1} \mathbf d \left( e^{(n-2p)\psi} \alpha_{i} \mathrm dx^{1} \wedge ... \wedge \widehat{\mathrm dx^{i}} \wedge ... \wedge \mathrm dx^{p} \right)\\ &= *_{g_\psi}^{-1} \Big( (n-2p)e^{(n-2p)\psi} \alpha_{i} \mathrm d\psi \wedge \mathrm dx^{1} \wedge ... \wedge \widehat{\mathrm dx^{i}} \wedge ... \wedge \mathrm dx^{p}\\ &\qquad+ e^{(n-2p)\psi} (\partial_j\alpha_i) \mathrm dx^j \wedge \mathrm dx^{1} \wedge ... \wedge \widehat{\mathrm dx^{i}} \wedge ... \wedge \mathrm dx^{p} \Big) \\ &\overset?= \underbrace{*_{g_\psi}^{-1}}_{= e^{-(n-2p)\psi} *_g} \Big[ e^{(n-2p)\psi} (n-2p) \mathrm d\psi \wedge \left(\alpha_{i} \mathrm dx^{1} \wedge ... \wedge \widehat{\mathrm dx^{i}} \wedge ... \wedge \mathrm dx^{p}\right)\\ &\qquad + (\partial_i\alpha_{i}) \mathrm dx^{1} \wedge ... \wedge \mathrm dx^{p} \Big] \\ &= -(n-2p) \ \iota_{\nabla\psi}\alpha + \delta, \\ \end{align*} where $\widehat{\mathrm dx^{i}}$ denotes the element that was left out and using that $*(X^\flat \wedge \alpha) = (-1)^p \iota_X(*\alpha)$.

(1) Where is the error?

(2) Is there an easy argument to deduce the formula from (cf. here) $$\text{div}_{g_\psi} X = \text{div}_{g} X + n e^{-2\psi} X(f)?$$

$\endgroup$
2
$\begingroup$

(1) The error indeed appears to occur at the equality marked with a $?$: If we denote $$\hat\ast := \ast_{g_\psi},$$ then in the calculation $\hat\ast^{-1}$ is applied to $d[e^{(n - 2 p) \psi} \ast \alpha]$, which is an $(n - p + 1)$-form. Thus, the inverse Hodge star operators $\ast^{-1}, \hat\ast^{-1}$ are related by $$\hat\ast^{-1} = e^{[n - (2 (n - p + 1))] \psi} \ast^{-1} = e^{(-n + 2p - 2) \psi} \ast^{-1}.$$ Thus, the total conformal factor that appears is $$e^{(-n + 2p - 2) \psi} \cdot e^{(n - 2p) \psi} = e^{-2 \psi}$$ as claimed. There's no need here, by the way, to resort to a coordinate computation here. Using the transformation rule for $\ast$, we can write the first few steps of the computation, again using hats $\hat\cdot$ to denote objects constructed from $\hat g := e^{2 \psi} g$, as $$\hat\delta \alpha = \hat\ast^{-1} d \hat\ast \alpha = \hat\ast^{-1} d [ e^{(n - 2 p) \psi} \ast \alpha] .$$

(2) The formula for the change of the divergence of a vector field under a conformal transformation is essentially equivalent to the specialization to $p = 1$ of the formula in this question: The vector field formula gives $$\widehat{\operatorname{div}} \,{\alpha^{\hat\sharp}} = \operatorname{div} \alpha^{\hat\sharp} + n \alpha^{\hat\sharp} \cdot f .$$ Unwinding definitions gives that the index-raising operators $\sharp, \hat\sharp$ are related by $$\alpha^{\hat\sharp} = e^{-2 \psi} \alpha^\sharp.$$ Then, substituting, applying the Leibniz rule for $\operatorname{div}$, rearranging, and replacing $\operatorname{div} \alpha^{\sharp}$ with $\delta \alpha$ and $\widehat{\operatorname{div}} \,{\alpha^{\hat\sharp}}$ with $\hat\delta \alpha$ recovers the $p = 1$ formula.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.